AUDIT FEES DETERMINANTS: THE IMPACT OF FIRM COMPLEXITY, MANAGERIAL OWNERSHIP, AND PARTNER ROTATION - Nurbaiti, Annisa; Thoi'ah, Naada; Fahlevi, Ali Riza; Khairunnisa (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2024)
The objective of this study is to understand the impact of firm complexity, managerial ownership, and audit partner rotation on audit fee simultaneous or partial of sector energy for the period of 2018-2022 listed on the Indonesia Stock Exchange. This research uses one of the latest IDX IC sector classifications for research objects, namely the energy sector with the latest year from 2018-2022. A quantitative method was employed in this study, utilizing 22 companies for five years, yielding 110 samples that were used. To determine the sample, in this study a method termed purposive sampling is employed. Methods that are used in this research are data panel regression using the Eviews 12 software application. According to the research's findings the firm complexity, managerial ownership, and audit partner rotation simultaneously affect audit fees in sector energy for the period of 2018-2022. Partially, in sector energy for the period of 2018-2022 the audit fee is positively affected by the complexity of the company; the audit fee is negatively affected by managerial ownership; and the audit fee is unaffected by audit partner rotation.